Effect of Stress and Self-esteem on QoL in General College Students (Medico Legal Update, 2019)
Background/Objectives: College students are in the transition period between adolescence and adulthood and need to lay the ground for emotional or financial independence. This study aimed to analyze the effects of general college students’ stress and self-esteem on their quality of life (QoL).Method/Statistical Analysis: This study was performed in a total of 200 students at S University in S City. With the exception of the questionnaires not returned or wrongly or not fully completed during the process of data collection (n=25), 175 questionnaires were finally analyzed. Before the survey, the participants in this study were given an explanation about the purport of the research and those consenting to participate in this study were asked to make a written consent and complete questionnaires, which were then returned. The collected data were analyzed using descriptive statistics and t-test, one-way ANOVA, Pearson’s correlation coefficient, and multiple linear regression.Findings: This study obtained the following results: first, the total score was 46.5 ± 18.4 for the socio-psychosocial well-being index (PWI), 30.2 ± 4.5 for self-esteem, and 91.0 ± 13.1 for QoL; second, QoL differed statistically significantly by the frequency of having breakfast per week (F=3.3, p=.02), and PWI (F=4.7, p=.003) and QoL (F=4.8, p=.003) differed statistically significantly by activity of daily; third, significant negative correlation was found between PWI and QoL(r=-.7, p